High-capacity silicon-based lithium battery negative electrode composite material and preparation method thereof

By designing a star-shaped structure of polyacrylic acid binder and a stacked structure of silicon powder and carbon nanotubes, the volume change problem of silicon-based lithium batteries during the working cycle is solved, and higher cycle stability and battery performance are achieved.

CN119775466AActive Publication Date: 2025-04-08DONGGUAN YOUFANG NEW ENERGY TECH CO LTD

Patent Information

Application Number
CN202411965141.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Severe volume changes in silicon-based lithium batteries during the working cycle lead to powdering, electrical contact loss, unstable solid electrolyte interfaces, and deterioration of reversibility of electrochemical cycles.

Method used

The polyacrylic binder with a star-shaped structure is designed and synthesized. The radial side chain contains multiple carboxyl groups, which can form a multi-hydrogen bond network structure in situ. Combined with the stacked structure of silicon powder and carbon nanotubes, the carbon layer and the star-shaped structure PAA binder jointly play the role of isolation, buffering and shielding.

Benefits of technology

It effectively reduces the volume expansion of the silicon-based dispersion layer, prevents direct contact between the silicon-based material and the electrolyte, reduces side reactions, and improves the cycle stability of the lithium battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119775466A_ABST
    Figure CN119775466A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium ion battery negative electrode materials, and relates to polyacrylic acid with a star-shaped structure and a preparation method thereof, application of the polyacrylic acid with the star-shaped structure as an adhesive in a battery negative electrode material, and a corresponding high-capacity silicon-based lithium battery negative electrode composite material and a preparation method thereof. A corresponding lithium battery negative electrode and a lithium battery are provided; firstly, a polyacrylic acid adhesive with a star-shaped structure is designed and synthesized, a linear side chain of the polyacrylic acid adhesive contains a plurality of carboxyl groups, and a self-repairing multiple hydrogen bond network structure can be formed in situ in the process of being matched with an electrode active material such as silicon powder or carbon powder; besides, the silicon-based material and the carbon-based material are sequentially stacked after being dispersed with water, the silicon-based material and the carbon-based material are filled with a polymer adhesive, the carbon-based material serves as a barrier between the silicon-based material and the electrolyte, and the carbon-based material and the polymer adhesive jointly inhibit volume expansion of the silicon-based material, so that volume expansion of the battery negative electrode in the using process is reduced, and the service life of the battery negative electrode is prolonged. Therefore, the cycling stability of the lithium battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of negative electrode materials for lithium ion batteries, and in particular to polyacrylic acid with a star-shaped structure and a corresponding high-capacity silicon-based lithium battery negative electrode composite material. Background Art

[0002] In order to meet the ever-increasing energy density requirements of future electrical energy storage and all-electric vehicles, various high-capacity electrode materials are currently being widely developed. Among them, silicon is considered to be the most promising candidate material for the next generation of lithium-ion batteries (LIBs) because of its high theoretical capacity, abundant natural resources, low electrochemical potential, and very high potential as anode material for lithium-ion batteries. The main problem of silicon as anode material for lithium-ion batteries is the drastic volume change during the working cycle, which leads to severe pulverization, electrical contact loss, unstable solid electrolyte interface, and deterioration of electrochemical cycle reversibility.

[0003] In order to solve the stability problem of the above-mentioned silicon-based materials, for the application scenarios of lithium-ion batteries, a large number of nanostructured silicon-based active materials, from zero-dimensional to three-dimensional silicon, especially complex layered structures (such as porous or hollow structures, core-shell structures, yolk-shell structures, etc.) have been proposed to solve the stability problem of silicon active materials. However, the preparation process of these complex silicon-based active materials is complicated and infeasible, and it is difficult to scale up. In addition, these modified nanostructured or porous materials usually have large specific surface area and inter-particle resistance, which leads to low initial coulomb efficiency (ICE) and small volume capacity, which is not suitable for practical application scenarios. Commercially available silicon microparticles (SiMP) are not only inexpensive, but also have higher ICE and energy density. Therefore, silicon microparticles are more promising negative electrode materials in practical industrial applications.

[0004] To solve the problem of drastic volume changes of silicon particles during the working cycle, dispersing silicon particles P in a polymer binder can buffer the volume expansion of silicon particles during charging. During deep cycles, the polymer binder acts as a flexible buffer, allowing the silicon particles to expand and break while maintaining good electrical connection and SEI stability on the surface of the composite material.

[0005] It can be seen that for silicon-based lithium batteries, polymer binders, as inactive substances in the battery, play a very important role in the formation of electrodes and the maintenance of their structures. In particular, they play a key role in maintaining structural stability and regulating volume expansion. The currently widely used carboxymethyl cellulose / styrene-butadiene rubber (CMC / SBR) composite binder has the advantages of high chemical stability, low cost, and environmental friendliness, but it is difficult to use in silicon-based materials due to its weak bonding strength. Polyacrylic acid (PAA) polymers and their modified products or derivatives have been widely studied due to their rich carboxyl groups and water solubility. There are a large number of sites that can form hydrogen bonds between PAA molecules, but since the topological structure of the polyacrylic acid (PAA) molecule is a linear structure, this limits the network structure formed in situ by the PAA binder during the preparation of silicon-based electrodes, so the adaptability to the rapid volume changes of highly active silicon particles needs to be improved.

[0006] The present invention starts with the topological structure design of PAA molecules, designs and synthesizes a star-structured PAA binder, and the radial side chains contain multiple carboxyl groups, including hydrogen bond acceptors and donors. When used in combination with electrode active materials such as silicon powder or carbon powder, a self-repairing multiple hydrogen bond network structure can be formed in situ, so it can adapt to different types of bonding matrices such as silicon-based and carbon-based. The existing hydrogen bond network structure has a better inhibitory effect on the rapid volume change that is prone to occur in silicon-based active materials. In addition, from the perspective of the arrangement of silicon-based and carbon-based materials, the silicon-based material and the carbon-based material are dispersed in water and then sequentially stacked. The two are filled with a polymer binder. The carbon-based material acts as a barrier between the silicon-based material and the electrolyte, and together with the polymer adhesive layer, it plays a role in inhibiting the volume expansion and crushing of the silicon active material, reducing the volume expansion of the electrode during use, thereby improving the cycle stability of the lithium battery. Summary of the invention

[0007] In view of the defects of the prior art, the present application invents a star-shaped polyacrylic acid and a preparation method thereof, as well as the use of the star-shaped polyacrylic acid as a binder in a battery negative electrode material, and a corresponding high-capacity silicon-based lithium battery negative electrode composite material and a preparation method thereof, as well as a corresponding lithium battery negative electrode and lithium battery, which solve the technical problems of the volume expansion of the electrode of the existing silicon-based lithium battery during use and the unsatisfactory cycle stability of the lithium battery.

[0008] This application is implemented through the following technical solutions:

[0009] In a first aspect, the present application provides a star-shaped polyacrylic acid, the structural formula of which is shown in the following formula (I) or (II), the structure comprising a core A and a linear side chain, the linear side chain comprising 2 to more carboxyl groups, the linear side chains being sequentially connected to the core A and the number of the linear side chains being ≥3, and the repeating structural unit n in the linear side chain being ≥1;

[0010]

[0011]

[0012] Preferably, the number of linear side chains is 3 to 4;

[0013] Preferably, the chemical structure of core A is selected from:

[0014] In a second aspect, the present application provides a method for preparing the above-mentioned star-structured polyacrylic acid, comprising: reacting 2-bromoisobutyryl bromide with a multi-side chain hydroxyl compound under the catalysis of an organic base to obtain a product I multi-arm intermediate, and then polymerizing the product I with tert-butyl acrylate to obtain a product II star-structured polyacrylic acid tert-butyl ester, and finally hydrolyzing the tert-butyl ester group in the product II under the catalysis of an organic acid to obtain the final product III star-structured polyacrylic acid.

[0015] Preferably, the polymerization reaction uses a transition metal catalyst, and more preferably, the transition metal catalyst is selected from CuBr.

[0016] Preferably, the polymerization reaction further uses a tertiary amine catalyst, and more preferably, the tertiary amine catalyst is selected from pentamethyldiethylenetriamine.

[0017] Preferably, the organic acid is selected from trifluoroacetic acid.

[0018] Preferably, the organic base is triethylamine.

[0019] Preferably, the multi-side chain hydroxy compound includes trishydroxyethyl isocyanurate or pentaerythritol.

[0020] Preferably, the process of reacting 2-bromoisobutyryl bromide with a multi-side chain hydroxy compound comprises: reacting 2-bromoisobutyryl bromide with a multi-side chain hydroxy compound at room temperature for at least 24 hours under the catalysis of an organic base; more preferably, the process of reacting 2-bromoisobutyryl bromide with a multi-side chain hydroxy compound further comprises: extracting, drying, and rotary evaporating the reaction product to remove the solvent, and using methanol to recrystallize and purify the crude product to obtain product I: a multi-arm intermediate.

[0021] Preferably, the process of polymerizing the product I multi-arm intermediate with tert-butyl acrylate comprises: polymerizing the product I multi-arm intermediate with tert-butyl acrylate, a transition metal catalyst, and a tertiary amine catalyst at 80 to 100° C. for at least 24 hours;

[0022] More preferably, the process of polymerizing the product I multi-arm intermediate with tert-butyl acrylate further comprises: removing metal ions from the reaction product by passing it through an alkaline alumina column to obtain product II: star-structured polytert-butyl acrylate.

[0023] Preferably, the process of hydrolyzing the tert-butyl ester group in the product II to obtain the final product III star-shaped polyacrylic acid comprises: precipitating the product II in an alcohol / water mixed solution, drying the precipitate and dissolving it again with an organic solvent, and adding an organic acid at a temperature of 0° C. to room temperature after dissolution, and the reaction time is at least 50 hours;

[0024] More preferably, the process of hydrolyzing the tert-butyl ester group in the product II to obtain the final product III star-shaped polyacrylic acid also includes: purifying the product precipitated from the reaction system by dialysis, and then freeze-drying the precipitated product to obtain the final product III star-shaped polyacrylic acid.

[0025] In a third aspect, the present application provides an adhesive, which at least comprises: the star-shaped polyacrylic acid described above;

[0026] Furthermore, the adhesive further comprises: a linear structure polymer. The linear structure polymer comprises a repeating structure of a hydrogen bond donor or a hydrogen bond acceptor;

[0027] Preferably, the repeating structure of the hydrogen bond donor or hydrogen bond acceptor includes: one or more of carboxyl, hydroxyl, amino, ester, ether, amide, carbamate, urea, and cyano groups;

[0028] More preferably, the linear structure polymer includes: one or a combination of linear structure polyacrylic acid, polyether, polyester, polyamide, polyurethane, polyurea, polyvinyl alcohol, and polyacrylonitrile.

[0029] In a fourth aspect, the present application provides a use, including: use of the above-mentioned binder as an electrode negative electrode material in the preparation of a silicon / carbon nanotube lithium battery negative electrode.

[0030] In a fifth aspect, the present application provides a high-capacity silicon-based lithium battery negative electrode composite material, comprising: a negative electrode current collector, a silicon-based material, a carbon-based material and the binder composition described above.

[0031] The negative electrode current collector is selected from the group consisting of electrolytic copper foil, rolled copper foil, double-sided smooth copper foil, double-sided rough copper foil, single-sided rough copper foil and porous copper foil, and the thickness of the negative electrode current collector does not exceed 20 μm;

[0032] Wherein, the silicon-based material is selected from silicon powder, and the particle size of the silicon powder does not exceed 1 μm;

[0033] Wherein, the carbon-based material is selected from carbon nanotubes (CNT) or multi-arm carbon nanotubes (MWCNT).

[0034] In a sixth aspect, the present application provides a method for preparing a silicon / carbon nanotube (Si / CNT) lithium battery negative electrode using the above-mentioned composite material, dissolving the binder composition in water, adding a silicon-based material to prepare a silicon-based dispersion, dissolving the binder composition in water, adding carbon nanotubes to prepare a carbon-based dispersion, first spraying the carbon-based dispersion onto the negative electrode collector by spraying, then alternately spraying the silicon-based dispersion and the carbon-based dispersion to obtain a stacked structure in which silicon layers and carbon layers are alternately arranged, and the last layer sprayed is the carbon layer. After the spraying is completed, the negative electrode collector sprayed with the silicon-based dispersion layer and the carbon-based dispersion layer is baked in a vacuum oven at 90 to 120°C for 1 to 3 hours, thereby preparing a stacked structure of a silicon / carbon nanotube (Si / CNT) lithium battery negative electrode.

[0035] Wherein, the binder composition used in the silicon-based dispersion is selected from: any one or a combination of the star-structured polyacrylic acid and the linear structure polymer containing a repeating structure of a hydrogen bond donor or a hydrogen bond acceptor as described above;

[0036] Wherein, the binder composition used in the carbon-based dispersion is selected from: any one or a combination of the star-structured polyacrylic acid and the linear structure polymer containing a repeating structure of a hydrogen bond donor or a hydrogen bond acceptor as described above;

[0037] Wherein, at least one of the silicon-based dispersion and the carbon-based dispersion selects the star-structured polyacrylic acid as a component of the adhesive composition;

[0038] Preferably, the repeating structure of the hydrogen bond donor or hydrogen bond acceptor includes: one or more of carboxyl, hydroxyl, amino, ester, ether, amide, carbamate, urea, and cyano groups;

[0039] Preferably, the linear polymer containing a repeating structure of a hydrogen bond donor or a hydrogen bond acceptor comprises: one or more combinations of linear polyacrylic acid, polyether, polyester, polyamide, polyurethane, polyurea, polyvinyl alcohol, and polyacrylonitrile;

[0040] More preferably, the linear polymer containing a repeating structure of a hydrogen bond donor or a hydrogen bond acceptor comprises any one or a combination of linear polyacrylic acid, polyvinyl alcohol or polyacrylonitrile.

[0041] Preferably, the silicon-based dispersion and the carbon-based dispersion are stirred separately for at least 12 h before spraying;

[0042] Preferably, the number of silicon layers in the laminated structure is ≥2, the number of carbon layers is ≥3, and the total number of laminated layers is not less than 5;

[0043] Preferably, the spray coating uses an ultrasonic spray coating method, using compressed air with a pressure of not less than 0.1 bar and an ultrasonic nozzle to spray the silicon-based dispersion or the carbon-based dispersant on the negative electrode current collector in sequence.

[0044] Preferably, the jetting rate of the ultrasonic nozzle is set at 0.05 to 0.5 mm / s;

[0045] Preferably, the jet frequency of the ultrasonic nozzle is not less than 90kHz;

[0046] Preferably, the spraying time is controlled between 10 and 20 minutes;

[0047] Preferably, the mass ratio of the silicon powder of the silicon layer to the total mass ratio of the carbon nanotubes of the carbon layer in the laminated structure is (8.0-9.0):(1.0-2.0).

[0048] In a seventh aspect, the present application provides a lithium battery negative electrode prepared by the preparation method described above.

[0049] In an eighth aspect, the present application provides a lithium battery, comprising: the lithium battery negative electrode described above.

[0050] The beneficial effects of the technical solution proposed by the present invention are:

[0051] The present invention designs and synthesizes a star-shaped PAA binder, wherein the radial side chains contain multiple carboxyl groups, including hydrogen bond acceptors and donors. During the composite use of the PAA binder and electrode active materials such as silicon powder or carbon powder, multiple reversible hydrogen bond networks can be formed in situ. On this basis, silicon powder and carbon nanotubes are respectively mixed with a binder containing star-structured PAA and water to prepare corresponding dispersions, and the carbon-based dispersion and the silicon-based dispersion are sprayed on battery-grade copper foil in sequence. The carbon layer of the carbon nanotubes and the star-structured PAA binder jointly act as a barrier between the silicon-based material and the electrolyte, playing the role of isolation, buffering and shielding. In particular, the star-structured PAA binder can form a denser hydrogen-bonded reversible cross-linking network through the side chain carboxyl group, which reduces the volume expansion of the silicon-based dispersion layer and prevents direct contact between the silicon-based material and the electrolyte, thereby effectively reducing the side reactions between the electrolyte and the silicon-based material. The lower volume change during the charge and discharge process of the battery can avoid irreversible loss of the electrode material and rapid attenuation of the capacity, reduce the volume expansion of the electrode during use, and thus improve the cycle stability of the lithium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of product I, product II and product III in the process of preparing star-structured polyacrylic acid in Example 1.

[0053] Figure 2Schematic diagram of the laminated structure of the negative electrode of a silicon / carbon nanotube (Si / CNT) lithium battery, wherein 1 is a copper foil layer, 2 is a carbon layer, and 3 is a silicon layer. DETAILED DESCRIPTION

[0054] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0055] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0056] If the specific experimental conditions are not specified in the examples, they are usually based on the conventional conditions in the field or the conditions recommended by the reagent company; the materials, reagents, etc. used in the examples can be purchased through commercial channels unless otherwise specified.

[0057] Sources of reagents used in the examples: Pentaerythritol (99%), triethylamine (TEA, 99.5%), 2-bromoisobutyryl bromide (98%) and cuprous bromide (CuBr, 99.9%) were purchased from Sigma-Aldrich. Trifluoroacetic acid (TFA, 99.5%), dichloromethane (DCM, 99.5%), tetrahydrofuran (THF, 99.5%), tert-butyl acrylate (99%), methanol (99.5%), pentamethyldiethylenetriamine (PMDETA, 99%) and N,N-dimethylformamide (DMF, 99.9%) were purchased from Aladdin. The resistivity of the deionized water used in the experiment was ≥18 MΩcm -1 (25℃).

[0058] Example 1

[0059] Star-shaped poly(isobutyl acrylate) was synthesized by atom transfer radical polymerization, and then poly(acrylic acid) with the corresponding structure was obtained by ester hydrolysis.

[0060] S1. At 0°C and in a nitrogen atmosphere, 2-bromoisobutyryl bromide (36.8 g) was added to a tetrahydrofuran solution containing triethylamine (168 g) and pentaerythritol (4.67 g). The above mixture was stirred for 24 hours and then kept at room temperature. The mixture was placed in a separatory funnel with 250 mL of dichloromethane and rinsed with 10% HCl, 5% NaHCO3 and deionized water in sequence. The organic phase was dried with MgSO4 and the solvent was removed by rotary evaporation. The crude product was recrystallized and purified using methanol and dried under vacuum to obtain product I: multi-arm intermediate.

[0061] S2, the prepared multi-arm intermediate (25mg), CuBr (40mg), pentamethyldiethylenetriamine (48mg), tert-butyl acrylate (18.2g) and solvent N, N-dimethylformamide (16mL) were mixed and sealed with an ampoule in a glove box. The ampoule was then immersed in a 90°C constant temperature oil bath under stirring to polymerize tert-butyl acrylate. After 24h, the reaction system was terminated by naturally cooling to room temperature. After the blue reaction product was passed through an alkaline alumina column, the copper ions therein were removed to obtain product II: a colorless, transparent, viscous substance.

[0062] S3. Precipitate the transparent viscous substance in a methanol / water mixed solution with a volume ratio of 1:1, and wash the precipitate three times with solvent N,N-dimethylformamide. Then dry the precipitated white product under vacuum. Finally, dissolve 1g of the precipitated product in solvent dichloromethane (40mL). Then, under a 0°C ice bath, gradually add 5mL of TFA to the dichloromethane solution that dissolves the star-shaped polyacrylic acid isobutyl ester. Keep and stir the mixture at 0°C for 2h, and then stir at room temperature for 48h. The star-shaped polyacrylic acid precipitated from the reaction system is purified by dialysis, and then the precipitated product is freeze-dried to obtain the final product III: star-shaped polyacrylic acid.

[0063] Product characterization: Products I and II were dissolved in CDCl3, and product III was dissolved in D2O. 1H-NMR (Bruker 400M) was used for nuclear magnetic resonance hydrogen spectrum characterization. The characterization results are shown in Figure 1 As shown, the molecular structures of intermediate products I, II and final product III were confirmed.

[0064] Example 2

[0065] The star-shaped polyisobutyl acrylate was synthesized by atom transfer radical polymerization, and then the polyacrylic acid with the corresponding structure was obtained by ester hydrolysis. The difference from Example 1 is that in step S1 of Example 2, 9.16 g of trimethylolpropane and 2-bromoisobutyryl bromide were used to react to prepare a multi-arm intermediate, and in step S2, 25 mg of the multi-arm intermediate was mixed with 12.9 g of tert-butyl acrylate to prepare a star-shaped polyisobutyl acrylate.

[0066] Example 3

[0067] Silicon / carbon nanotube (Si / CNT) lithium battery negative electrode was prepared by ultrasonic spraying. Silicon powder Brofos-Si-100 (0.48 g) with an average particle size of 100 nm and the star-shaped polyacrylic acid binder (53.3 mg) prepared in Example 1 were dissolved in 42 mL of deionized water and stirred for 12 h to prepare a silicon-based dispersion. Subsequently, a carbon-based dispersion was prepared by dissolving (0.06 g) carbon nanotubes (A-CNT, Defang Nano) and (6.7 mg) the star-shaped polyacrylic acid binder prepared in Example 1 in 34 mL of deionized water using a homogenizer and then stirring for 12 h. Compressed air (0.1 bar) and an ultrasonic nozzle were used to spray a carbon-based dispersion and a silicon-based dispersion in sequence on a 6μm double-sided photovoltaic-grade copper foil (Tongling Huilifengke Electronic Materials). A uniform carbon layer and a silicon layer were sprayed on a 70μm×100mm copper foil substrate area. The spray rate, frequency, and spray time of the ultrasonic nozzle were set to 0.1mm / s, 120kHz, and 15min, respectively. After spraying, the mixture was baked in a vacuum oven at 105°C for 2h, and finally a 5-layered Si / CNT battery negative electrode was obtained, of which 3 layers were silicon layers and 4 layers were carbon layers. The mass ratio of the silicon layer and the carbon layer in each layer is 28.33% and 3.75%. In the final prepared layered Si / CNT lithium battery negative electrode, the total mass ratio of the silicon layer to the carbon layer is (8.5:1.5). The schematic diagram of the layered structure of the Si / CNT lithium battery negative electrode prepared in Example 3 is shown in FIG. Figure 2 shown.

[0068] Example 4

[0069] The preparation method of the Si / CNT battery negative electrode is the same as that of Example 3, except that Brofos-Si-100 Si powder (0.48 g) with an average particle size of 100 nm and the star-shaped polyacrylic acid binder (53.3 mg) prepared in Example 2 are dissolved in 42 mL of deionized water and stirred for 12 h to prepare the silicon-based dispersion. The carbon-based dispersion is prepared by dissolving (0.06 g) of carbon nanotubes (A-CNT, Defang Nano) and (6.7 mg) of the star-shaped polyacrylic acid binder prepared in Example 2 in 34 mL of deionized water using a homogenizer and stirring for 12 h.

[0070] Example 5

[0071] The preparation method of the Si / CNT battery negative electrode is the same as that in Example 3, except that Brofos-Si-100 Si powder (0.48 g) with an average particle size of 100 nm and the star-structured polyacrylic acid (53.3 mg) binder prepared in Example 1 and (10 mg) polyvinyl alcohol binder are dissolved in 42 mL of deionized water and stirred for 12 h to prepare a silicon-based dispersion.

[0072] Example 6

[0073] The preparation method of the Si / CNT battery negative electrode is the same as that in Example 3, except that Brofos-Si-100Si powder (0.48 g) with an average particle size (100 nm) and the star-structured polyacrylic acid (53.3 mg) binder and (8 mg) polyacrylonitrile binder prepared in Example 1 are dissolved together in 42 mL of deionized water and stirred for 12 h to prepare a silicon-based dispersion.

[0074] Example 7

[0075] The preparation method of the Si / CNT battery negative electrode is the same as that in Example 3, except that Brofos-Si-100Si powder (0.48 g) with an average particle size (100 nm) and the star-structured polyacrylic acid (53.3 mg) binder prepared in Example 1 and (6 mg) linear PAA binder are dissolved together in 42 mL of deionized water and stirred for 12 h to prepare a silicon-based dispersion.

[0076] Example 8

[0077] The preparation method of the Si / CNT battery negative electrode is the same as that of Example 3, except that Brofos-Si-100 Si powder (0.48 g) with an average particle size of 100 nm and the star-shaped polyacrylic acid binder (53.3 mg) prepared in Example 1 and 6 mg of linear PAA binder are dissolved in 42 mL of deionized water and stirred for 12 h to prepare the silicon-based dispersion. The carbon-based dispersion is prepared by dissolving (0.06 g) of carbon nanotubes (A-CNT, Defang Nano) and (6.7 mg) of the star-shaped polyacrylic acid binder prepared in Example 1 and 3 mg of linear PAA binder in 34 mL of deionized water using a homogenizer and then stirring for 12 h.

[0078] Example 9

[0079] The method was the same as in Example 3, except that silicon powder Brofos-Si-100 (0.48 g) with an average particle size of 100 nm and the star-shaped polyacrylic acid (53.3 mg) prepared in Example 1 were dissolved in 42 mL of deionized water and stirred for 12 h to prepare the silicon-based dispersion. Carbon-based dispersion was prepared by dissolving (0.06 g) carbon nanotubes (A-CNT, Defang Nano) and (6.7 mg) linear PAA binder in 34 mL of deionized water using a homogenizer and stirring for 12 h.

[0080] Example 10

[0081] The method is the same as that of Example 3, except that silicon powder Brofos-Si-100 (0.48 g) with an average particle size of 100 nm and linear PAA binder (53.3 mg) are dissolved in 42 mL of deionized water and stirred for 12 h to prepare a silicon-based dispersion. Carbon-based dispersion is prepared by dissolving (0.06 g) carbon nanotubes (A-CNT, Defang Nano) and star-structured polyacrylic acid (6.7 mg) prepared in Example 1 in 34 mL of deionized water using a homogenizer and stirring for 12 h.

[0082] Comparative Example 1

[0083] The method was the same as in Example 3, except that silicon powder Brofos-Si-100 (0.48 g) with an average particle size of 100 nm and linear PAA binder (53.3 mg) were dissolved in 42 mL of deionized water and stirred for 12 h to prepare the silicon-based dispersion. Carbon-based dispersion was prepared by dissolving (0.06 g) carbon nanotubes (A-CNT, Defang Nano) and linear PAA binder (6.7 mg) in 34 mL of deionized water using a homogenizer and then stirring for 12 h.

[0084] Comparative Example 2

[0085] The silicon powder-carbon nanotube composite dispersion was prepared by dissolving (0.06 g) carbon nanotubes (A-CNT, Defang Nano Company), silicon powder Brofos-Si-100 (0.48 g) with an average particle size of 100 nm and the star-shaped polyacrylic acid binder (60 mg) prepared in Example 1 in 76 mL of deionized water and stirring for 12 h. The silicon powder-carbon nanotube composite dispersion was sprayed on a 6 um double-sided photovoltaic cell grade copper foil (Tongling Huilifengke Electronic Materials) using compressed air (0.1 bar) and an ultrasonic nozzle, and a uniform silicon powder-carbon nanotube composite layer was formed by spraying on a 70 μm × 100 mm copper foil substrate area. The spray rate, frequency, and spray time of the ultrasonic nozzle were set to 0.1 mm / s, 120 kHz, and 15 min, respectively. After the spraying was completed, it was baked in a vacuum oven at 105 ° C for 2 h, and finally the Si / CNT electrode of the silicon powder-carbon nanotube composite layer was sprayed.

[0086] Comparative Example 3

[0087] The silicon powder-carbon nanotube composite dispersion was prepared by dissolving (0.06 g) carbon nanotubes (A-CNT, Defang Nano), silicon powder Brofos-Si-100 (0.48 g) with an average particle size of 100 nm and linear PAA binder (60 mg) in 76 mL of deionized water by a homogenizer and stirring for 12 h. The silicon powder-carbon nanotube composite dispersion was sprayed on a 6 μm double-sided photovoltaic cell grade copper foil (Tongling Huilifengke Electronic Materials) using compressed air (0.1 bar) and an ultrasonic nozzle, and a uniform silicon powder-carbon nanotube composite layer was sprayed on a 70 μm×100 mm copper foil substrate area. The spray rate, frequency, and spray time of the ultrasonic nozzle were set to 0.1 mm / s, 120 kHz, and 15 min, respectively. After spraying, it was baked in a vacuum oven at 105°C for 2 h, and finally a Si / CNT electrode with a silicon powder-carbon nanotube composite layer was sprayed.

[0088] The electrochemical performance test methods of Examples 3-10 and Comparative Examples 1-3 are as follows, and the test results are listed in Table 1.

[0089] The baked copper foil current collector was cut into a circular pole piece with a diameter of 16 mm. A metal lithium sheet was used as the positive electrode, a porous polypropylene film Celgard2400 was used as the separator, and the electrolyte was 1.0M LiPF6 (the electrolyte solvent was a mixture of ethylene carbonate / dimethyl carbonate with a volume ratio of 1:1). The half-cell was assembled and manufactured in a glove box under high-purity argon. At the same time, the H2O and O2 content in the air inside the glove box was less than 10ppm.

[0090] The electrochemical impedance test was first performed using an electrochemical workstation to test the open circuit potential. After 300 seconds, the impedance test (EIS) was performed after the open circuit potential stabilized. The initial potential was the open circuit potential value recorded previously. The frequency range of the impedance test was 10 -2 Hz~10 5 Hz, with a signal amplitude of 10 mV. This is to examine the kinetics and resistance of each interface. EIS is used to analyze the charge transfer mechanism that promotes Li ion diffusion, and the Warburg impedance (σ w ), which corresponds to the resistance to lithium ion diffusion at the electrode, according to the Warburg impedance (σ w ) and the following formula (1) are used to calculate the lithium ion diffusion coefficients corresponding to the Si / CNT electrode assembled batteries prepared in different embodiments and comparative examples.

[0091]

[0092] Among them, σ w is the Warburg impedance coefficient of the battery impedance obtained by EIS test, and D, R, T, A, m, F and C correspond to the diffusion coefficient of lithium ions, gas constant, operating temperature, electrode area, number of electrons, Faraday constant and molar Li ion concentration, respectively. The lithium ion diffusion coefficients of the Si / CNT electrode assembled batteries of Examples 3-10 and Comparative Examples 1-3 are calculated and the results are listed in Table 1.

[0093] Table 1

[0094]

[0095]

[0096] The battery was cycled at 0.1-1.5 V (vs. Li / Li) using a WBCS 3000 battery cycler (WonA Tech). + ) voltage range, the battery performance assembled by the Si / CNT electrodes of different embodiments and comparative examples was evaluated in a 25°C thermostat. Specifically, the initial energy density of the battery was tested, the energy density of the battery after 10 constant current charge and discharge cycles at a current density of 100 mA / g was tested, and then the energy density of the battery after 190 constant current charge and discharge cycles at current densities of 200 mA / g and 2000 mA / g was tested, so as to evaluate the applicability of the Si / CNT electrodes prepared in Examples 3-10 and Comparative Examples 1-3 in lithium ion batteries, and the results are listed in Table 1.

[0097] The performance test data of Examples 3-10 and Comparative Examples 1-3 are shown in Table 1, which fully demonstrates the excellent effect of the present invention on improving the cyclability of silicon-based negative electrodes by introducing a star-shaped polyacrylic acid binder and stacking silicon-based materials and carbon-based materials. In terms of initial energy density, the silicon negative electrode can theoretically provide an energy density of 4200mAh / g, which is more than 10 times that of carbon-based graphite. Silicon-based materials are mixed with carbon-based materials and binders to obtain Si / CNT electrodes. The initial energy density of the batteries prepared in this way is between 3000 and 4000mAh / g, and no significant difference is observed between different embodiments and comparative examples.

[0098] After the battery was cycled 10 times at 100 mA / g and then 190 times at 200 mA / g, or 190 times at 2000 mA / g, the Si / CNT electrodes prepared in Examples 3-10 showed very good capacity retention, which was attributed to two aspects. On the one hand, the carbon layer composed of carbon nanotubes was used to physically isolate the silicon powder of the silicon layer from the electrolyte, minimizing the reaction of the silicon-based material, thereby enhancing the cycle stability of the battery; on the other hand, a star-shaped polyacrylic acid binder was used in the Si / CNT electrode. Compared with the linear polyacrylic acid, the binder with a star-shaped topological molecular structure provided a higher buffering capacity to reduce volume expansion, and the cross-linked network structure formed by the interaction between the side chain carboxyl-COOH was denser than that of the linear polyacrylic acid, thereby reducing the side reaction of the silicon-based material with the electrolyte and improving the cycle life and stability. From the comparison between comparative example 1 and examples 3-10, it can be seen that the battery cycle stability effect of the star-shaped polyacrylic acid binder for the battery negative electrode Si-based material or carbon-based material is better. From the comparison between comparative example 2 and examples 3-10, it can be seen that the battery cycle stability effect of the laminated structure Si / CNT electrode prepared by spraying the CNT layer and the Si layer on the copper foil in sequence is better. The CNT layer is designed on both sides of the silicon-based material to play a buffering role, inhibiting the overall volume expansion of the electrode, and can also play a synergistic role with the star-shaped polyacrylic acid binder to significantly delay the volume expansion of the silicon-based material. During the operation of the battery, a lower degree of volume change will avoid irreversible loss of the electrode material and rapid attenuation of capacity, thereby improving the cycle stability effect of the battery.

[0099] In addition, from the Warburg impedance coefficient obtained by EIS test and the lithium ion diffusion coefficient calculated, the molecular topology of the negative electrode binder PAA has a great influence on the lithium ion diffusion coefficient. Examples 3-10 and Comparative Example 2 partially or completely use the star-shaped polyacrylic acid binder prepared in Example 1 or Example 2, and the corresponding Si / CNT electrode has a higher lithium ion diffusion coefficient. Even if the comparative example 2 with a changed laminated structure has a lithium ion diffusion coefficient of 9.4×10 -13 cm 2 / s, which is much higher than that of conventional linear PAA binders. This is related to the fact that the side chains of the star-shaped polyacrylic acid binder contain carboxyl groups COOH and form hydrogen bonds with each other, thereby constructing a dense reversible hydrogen bond cross-linking network.

[0100] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on parts thereof. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention. Although the above describes the specific implementation methods of the present invention, it is not intended to limit the protection scope of the present invention. Those skilled in the art should understand that, based on the technical solution of the present invention, various modifications or deformations that can be made by those skilled in the art without creative labor are still within the protection scope of the present invention.

Claims

1. A star-shaped polyacrylic acid, characterized in that: Its structural formula is shown in the following formula (I) or (II), the molecular structure comprises a core A and a linear side chain, the linear side chain comprises 2 to more carboxyl groups, the linear side chains are sequentially connected to the core A and the number of the linear side chains is ≥3, and the repeating structural unit n in the linear side chain is ≥1; The chemical structure of core A is selected from: or 2. A method for preparing star-shaped polyacrylic acid, characterized in that: The preparation method comprises: reacting 2-bromoisobutyryl bromide with a multi-side chain hydroxyl compound under the catalysis of an organic base to obtain a product I multi-arm intermediate, polymerizing the product I with tert-butyl acrylate to obtain a product II star-shaped polytert-butyl acrylate, and finally hydrolyzing the tert-butyl ester group in the product II under the catalysis of an organic acid to obtain a final product III which is the star-shaped polyacrylic acid according to claim 1; Wherein, the polymerization reaction uses a transition metal catalyst; The polymerization reaction also uses a tertiary amine catalyst; The organic acid is selected from trifluoroacetic acid; The organic base is triethylamine; The poly-side chain hydroxy compound is selected from: trishydroxyethyl isocyanurate or pentaerythritol.

3. An adhesive, characterized in that: The adhesive at least includes the star-structured polyacrylic acid according to claim 1.

4. The adhesive according to claim 3, characterized in that: The binder also includes a linear structure polymer comprising a repeating structure of a hydrogen bond donor or a hydrogen bond acceptor.

5. A use, characterized in that: Use of the binder described in any one of claims 3 to 4 as an electrode negative electrode material in the preparation of a silicon / carbon nanotube lithium battery negative electrode.

6. A high-capacity silicon-based lithium battery negative electrode composite material, characterized in that: The composite material comprises: a negative electrode current collector, a silicon-based material, a carbon-based material and the binder composition according to any one of claims 3 and 4.

7. A method for preparing a negative electrode of a silicon / carbon nanotube lithium battery, characterized in that: The composite material according to claim 6 is used, and the preparation method comprises: dissolving the binder composition in water, adding a silicon-based material to prepare a silicon-based dispersion, dissolving the binder composition in water, adding carbon nanotubes to prepare a carbon-based dispersion, spraying the carbon-based dispersion onto the negative electrode current collector by spraying, then alternately spraying the silicon-based dispersion and the carbon-based dispersion to obtain a laminated structure in which silicon layers and carbon layers are alternately arranged, the last layer sprayed is a carbon layer, and after the spraying is completed, the negative electrode current collector sprayed with the silicon-based dispersion layer and the carbon-based dispersion layer is baked in a vacuum oven at 90 to 120° C. for 1 to 3 hours, thereby preparing a laminated structure of silicon / carbon nanotube lithium battery negative electrode; Wherein, the binder composition used in the silicon-based dispersion is selected from: any one or a combination of two of the star-structured polyacrylic acid and a linear structure polymer containing a repeating structure of a hydrogen bond donor or a hydrogen bond acceptor; Wherein, the binder composition used in the carbon-based dispersion is selected from: any one or a combination of two of the star-structured polyacrylic acid and the linear structure polymer containing a repeating structure of a hydrogen bond donor or a hydrogen bond acceptor; Wherein, at least one of the silicon-based dispersion and the carbon-based dispersion selects the star-structured polyacrylic acid as a component of the adhesive composition; The repeating structure of the hydrogen bond donor or hydrogen bond acceptor includes: one or more of carboxyl group, hydroxyl group, amino group, ester group, ether group, amide group, carbamate group, urea group and cyano group.

8. The method for preparing a negative electrode of a silicon / carbon nanotube lithium battery according to claim 7, characterized in that: Stir the silicon-based dispersion and the carbon-based dispersion separately for at least 12 h before spraying; The stacked structure has ≥2 silicon layers, ≥3 carbon layers, and the stacked structure has no less than 5 layers in total.

9. A lithium battery negative electrode, characterized in that: The compound is prepared by the preparation method according to any one of claims 7 and 8.

10. A lithium battery, characterized in that: include: The lithium battery negative electrode according to claim 9.

Citation Information

Patent Citations

  • Negative pole piece as well as preparation method and application thereof

    CN111540882A

  • Integrated negative electrode material composed of 3D current collector, carbon layer and silicon layer

    CN115394956A

  • Silicon-based negative electrode binder with topological three-dimensional structure, negative electrode plate, preparation method of negative electrode plate and battery

    CN117038991A

  • Polyfunctional compounds and uses as implant materials

    US20090131551A1

  • Polyacid-functionalized porous membranes, related methods, and related polyacid polymers

    US20180117538A1

Cited By

  • Star-shaped polymers and their preparation methods, binders, electrode materials, electrodes and batteries

    CN122563031A